(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2026)
The study examines the liberal discourse in the podcast "Al-Bilad" as a digital tool for representing the Palestinian issue. It hypothesizes that audio blogs create counter-narratives that challenge mainstream media and promote critical political awareness. The study uses media dependence theory and discourse analysis to analyze 11 episodes from 2021 to 2024. Results show a dominant rational and emotional liberation discourse, deconstructing the Zionist narrative and highlighting the Palestinian as a historical actor. Podcasts are seen as a strategic means of resistance digital media, restoring consideration for liberation issues within the digital space.